IMPLEMENTASI ETIKA BISNIS ISLAM DALAM MENINGKATKAN KUALITAS UMKM WARUNG MAKAN (STUDI PADA WARTEG GRAND BAHARI SAWANGAN LAMA - Bekti Anugrah Parsetyo; Siti Jamilah (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study aims to explore the implementation of Islamic business ethics in enhancing the operational quality and sustainability of micro, small, and medium enterprises (MSMEs), with a case study of Warteg Grand Bahari in Sawangan Lama, Indonesia. Islamic business ethics—rooted in principles such as honesty (ṣidq), justice (ʿadl), trustworthiness (amanah), social responsibility, and avoidance of riba—are not only normative values but can be applied practically in daily business operations. Employing a qualitative descriptive approach, data were collected through in-depth interviews, direct observations, and documentation. The findings reveal that the business consistently applies ethical principles in various aspects, including halal food management, fair pricing, employee welfare, and transparent customer service. Moreover, ethical conduct is reinforced by the owner’s entrepreneurial competence, spiritual motivation, and the formation of a value-based organizational culture. Despite financial and competitive challenges, the enterprise remains sustainable through adaptive strategies grounded in Islamic values. This study contributes theoretically by offering an integrative model of ethical entrepreneurship and practically by providing a replicable framework for MSMEs seeking value-based business practices. It is concluded that the integration of ethics, competence, organizational culture, and spirituality fosters business resilience, customer loyalty, and long-term sustainability in a sharia-compliant context.Keywords: Business Ethics, Islamic Entrepreneurship, Halalan Tayyiban, MSMEs, Spiritual Business